The Justification of Open Surgical Repair for an Abdominal Aortic Aneurysm: A Retrospective Comparison of Outcomes of Endovascular Aneurysm Repair and a Brief Review of the Literature - Ümit Arslan; Ziya Yıldız; İbrahim Pir; Çağrı Aykut (Life)
Background: Abdominal aortic aneurysms (AAAs) are life-threatening conditions that require timely intervention to prevent rupture. Endovascular aneurysm repair (EVAR) is preferred due to faster recovery and lower perioperative risk; however, intraoperative failure and long-term complications highlight the continued significance of open surgical repair (OSR) and the need for improved risk assessment. Methods: This retrospective study analyzed data from 210 patients who underwent EVAR (n = 163) or OSR (n = 47) at a single center. Clinical characteristics, complications, reintervention rates, and 30-day mortality were recorded. EVAR-to-OSR conversion and mortality predictors in AAA treatments were identified. Results: The overall mortality rate was 9.5% (20/210 patients), with 12 patients (7.3%) in the EVAR group and 8 patients (17%) in the OSR group (p = 0.085). Five patients required early and six required late conversion to open surgery. In follow-ups beyond 30 days, the reintervention rate for EVAR was higher (HR: 1.2, 95% CI: 0.4–3.6; p = 0.754). According to the multivariable analysis, rupture (p = 0.045), female sex (p = 0.018), body weight (p = 0.003), and aortic size index (p = 0.019) were significant predictors of mortality, whereas OSR was not (p = 0.212). Conclusions: Treatment optimization requires a balanced approach, integrating both EVAR and OSR based on patient-specific factors. Maintaining expertise in both techniques is essential to ensure the best possible outcomes, and OSR should remain a viable option when clinically indicated.